Impact of Nanotechnology as Irrigation Protocol for Revascularization of Immature Necrotic Teeth on Postoperative Pain - Mohammed Abd Al-Mawla Mohammed,; Omar Fahim,; Dalia Moukarab, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aim: This study aimed at comparing postoperative pain following photosensitized chitosan nanoparticles versus conventional protocol of disinfection technique in regenerative endodontic treatment (RET) of necrotic immature teeth. Methods: Double-blind randomized clinical research evaluated the disinfection efficiency of sodium hypochlorite (1.5%) versus photosensitized chitosan nanoparticles (2%) in 22 patients regarding postoperative pain. Results: The clinical trial demonstrated no statistically significant difference in postoperative pain between both disinfection techniques. Conclusion: photosensitized chitosan nanoparticles has a positive effect on the postoperative pain in revascularization of necrotic immature teeth.